العوامل السوسيو اقتصادية وانعكاساتها على الهدر المدرسي في المدرسة الجزائرية - العقون، صليحة, غنايم، منال (جامعة الوادي university of Eloued, 2021)
الملخص: تهدف هذه الدراسة إلى ما يلي: • تسليط الضوء على ظاهرة الهدر المدرسي والتعريف بها. • التعرف على انعكاس العوامل السوسيو اقتصادية على الهدر المدرسي. • التوعية بالتأثيرات السلبية للتنشئة الاجتماعية الخاطئة على التلميذ و التنويه إلى الحد منها في مقترحات الدراسة. • معرفة دور المستوى الاقتصادي للأسرة في تسرب التلميذ. • توصل إلى وضع الحلول التي يمكن أن تتبع للتقليل من ظاهرة التسرب أو الهدر المدرسي أو الحد منها. ولقد كانت صياغة التساؤل الرئيسي للدراسة كالتالي: ما هي انعكاسات العوامل السوسيو اقتصادية على الهدر المدرسي في المدرسة الجزائرية؟ ومن هذه الإشكالية يتفرع منها الأسئلة الفرعية التالية: - ما مدى تأثير المشاكل الأسرية على الهدر المدرسي؟ - ما مدى تأثير الطلاق على الهدر المدرسي؟ - ما مدى تأثير البطالة على الهدر المدرسي؟ - ما مدى تأثير المستوى المعيشي على الهدر المدرسي؟ ولقد تم الاعتماد على المنهج الوصفي وأجريت الدراسة على مستوى المتربصين المتسربين تعليميا الموجودين بمركز التكوين المهني والتمهين بالدبيلة وبالتحديد على التلاميذ المتسربين المشهود لهم بانقطاع الكلي من الدراسة و مزاولة التكوين و التربصات المهنية والمقدر عددهم بــ 112 متربص. حيث تمت دراسة مسحية للعينة بعد إقصاء 07 متحصلين على شهادة البكالوريا. وتم التوصل إلى النتائج التالية: - تم التأكيد بوجود انعكاسات للعوامل الاجتماعية على الهدر المدرسي. - تم التأكيد بوجود انعكاسات للعوامل الاقتصادية على الهدر المدرسي. The summary is in english: This study aims to: • Highlighting the phenomenon of school dropout and introduces it. • Recognizing the impact of socio-economic factors on school dropout. • Awareness of the negative effects of the wrong social upbringing on the student and noting to reduce it in the study proposals. • Recognizing the role of the economic level of the family in the dropout of the student. • Finding solutions that can be followed to reduce or eliminate the phenomenon of school dropout. The main question of the study was formulated as follows: What are the implications of socio-economic factors on school dropout in the Algerian school? From this problem, the following sub-questions arise: What is the impact of family problems on school dropout? What is the impact of divorce on school dropouts? What is the impact of unemployment on school dropouts? What is the impact of the standard of living on the school dropout? The descriptive approach was relied upon and the study was conducted at the level of the educational dropout stalkers who are present at the (Mujahid for Muqaddam Mabrouk) in Debila, specifically on the dropout students who are known to have completely dropped out of school and practice professional training and apprenticeships. A total of 112 students. They have been studied after eliminating 7 of them who have obtained a baccalaureate degree. The following results were obtained: - It was confirmed that there are reflections of social factors on school dropout. - It was confirmed that there are reflections of economic factors on school
مذكرة ماستر علم اجتماع تخصص علم اجتماع التربية
Keywords: الهدر المدرسي، التأخر الدراسي، التسرب الدراسي; Décrochage scolaire, retard scolaire, décrochage scolaire; School dropouts, school tardiness, school dropouts